2000
DOI: 10.1037/0021-843x.109.4.743
|View full text |Cite
|
Sign up to set email alerts
|

The paradox of normal neuropsychological function in schizophrenia.

Abstract: Mounting evidence suggests that compromised neurocognitive function is a core feature of schizophrenia. However, some studies have found neuropsychologically normal schizophrenia patients. To address this apparent contradiction, we blindly rated individual neuropsychological profiles of 75 schizophrenia patients and 91 control participants on the basis of methods developed by L. J. Seidman, S. V. Faraone, W. S. Kremen, J. R. Pepple, M. J. Lyons, and M. T. Tsuang (1993). Almost one-quarter of the patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
131
3
12

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(157 citation statements)
references
References 54 publications
(79 reference statements)
11
131
3
12
Order By: Relevance
“…Many studies have found a small subgroup of patients whose performance puts them within the normal range of NP functioning. The prevalence of NP normality, however, has been variable across studies, ranging from 0% (Bozikas et al, 2006;Wilk et al, 2005) to 82% (Torrey et al, 1994), with the majority of studies reporting rates closer to 25% (Bryson et al, 1993;Kremen et al, 2000;Palmer et al, 1997;Rund et al, 2006). These discrepancies are likely caused by sample characteristics and how normality is operationalized.…”
Section: Introductionmentioning
confidence: 91%
“…Many studies have found a small subgroup of patients whose performance puts them within the normal range of NP functioning. The prevalence of NP normality, however, has been variable across studies, ranging from 0% (Bozikas et al, 2006;Wilk et al, 2005) to 82% (Torrey et al, 1994), with the majority of studies reporting rates closer to 25% (Bryson et al, 1993;Kremen et al, 2000;Palmer et al, 1997;Rund et al, 2006). These discrepancies are likely caused by sample characteristics and how normality is operationalized.…”
Section: Introductionmentioning
confidence: 91%
“…Although no cognitive profile is recognized as a "signature" of SZ, patients typically demonstrate especially severe impairments of complex attention, psychomotor speed, new learning/memory, and abstraction or executive functioning (Bilder et al 2000;Bowie and Harvey 2005;Censits et al 1997;Flashman and Green 2004;Heinrichs 2005;Hill et al 2002). Milder impairments of these abilities have been found in SZ patients who appear cognitively normal (Kremen et al 2000). Yet while their presence and persistence are well-documented, the specificity of these cognitive deficits remains unclear.…”
Section: Introductionmentioning
confidence: 98%
“…However, not all psychotic patients show cognitive impairment (Kremen et al, 2000). A recent epidemiological study of first-admission patients with psychotic disorders estimated that as many as 16% of schizophrenic, 20% schizoaffective, 42% of bipolar, and 42% of depressed patients may not be cognitively impaired .…”
Section: Introductionmentioning
confidence: 99%